ANALISIS PENGARUH PENGGUNAAN METODE ECONOMIC ORDER QUANTITY ( EOQ ) TERHADAP PENURUNAN OVER STOK PERSEDIAAN OBAT PADA RUMAH SAKIT ASSALAM GEMOLONG SRAGEN - Samrotun, Yuli Chomsatu (PARADIGMA, 2010)
The problem that discussing in this research is overstock case of medicine supplies in Common Hospital of Assalam Gemolong Sragen in year of 2008 where supply management by conventional method. The Suggest for the problem is using Economic Order Quantity (EOQ) method to make overstock degradation of the medicine stok.Intention of this research is : 1) Knowing supply management medicinize with Economic Order Quantity method (EOQ) at Common Hospital of Assalam Gemolong Sragen 2) Knowing influence after use Economic Order Quantity (EOQ) method in lessening over stok in Common Hospital Assalam Gemolong Sragen. This Research represent the descriptive research type, data utilized is quantitative. The object research is the method of ordering medicinize supply in Common Hospital Assalam Gemolong Sragen by Economic Order Quantity (EOQ). The data used is 1) Primary Data; and 2) Secondary Data. Population : The note of medicinize supply during year 2008 amounting to 736 type. Sampel as much 8 type medicinize passing technique of purposive sampling. Technique of the data collecting that using in this research is 1) Documentation 2) Interview; 3) Book Study. Methode Analyse the Data utilized by EOQ method. From calculation result analyse from the data, This is the conclusion: from 8 sampel taken by passing EOQ method compared to Conventional method of result that entire Conventional compared to smaller method EOQ calculation with the following difference result : Amoxan: 2.176 for the price of Rp.6.038.600,-, Cendantron Hypodermic: 870 for the price of Rp.14.966.666,-, Clinjos 300 Mg: 17.477 for the price of Rp.79.158.239,-, Sanmol 500 Mg: 14.465 for the price of Rp.2.755.455,-, Inbion: 4.324 for the price of Rp.3.659.572,-, Intunal F: 3.926 for the price of Rp.1.800.607,-, Vitamam: 978 for the price of Rp.445.994,-, and Alcohol: 1.230.908 for the price of Rp.2.089.850,-; Besides minimizing the stock and supply expense, EOQ manager own the guidance how and when ordering can be done as considering minimum and maximum supply, so that EOQ more than able to take care of the supply stability and avoid the existence of over stock. Keywords : EOQ, Medicine Stok, Overstock